Ecclesial recognition with Hegelian philosophy, social psychology & continental political theory : an interdisciplinary proposal - Lim, Timothy Teck Ngern (Theology and mission in world Christianity,, 2017)
Ecclesial Recognition proffers a framework for churches to accept the legitimacy and authenticity of each other as the Church in the dialogical process towards fuller communion. Typically, 'recognition' and its reception investigate theologically the sufficiency of creeds as ecumenical statements of unity, the agreeability of essential sacramentality of the church, and the recognition of its ministries as the churches' witness of the gospel. This monograph conceives ecclesial recognition as an intersubjective dynamics of inclusion and exclusion amid identity formation and consensus development, with insights from Hegelian philosophy, group social psychology, and the Frankfurt School Axel Honneth's political theory. The viability of this interdisciplinary approach is demonstrated from the French Dominican Yves Congar's oeuvre, with implications for intra-Communion and inter-Church relations. \'Dr Lim examines philosophical recognition theory, group social psychology and political recognition theory to analyse the non-theological impasses confronting the whole ecumenical movement.\' - Rev Dr Trevor Hoggard, Director English-speaking Ministries, Methodist Church of New Zealand. \'Lim masterfully argues for the viability of an interdisciplinary approach to ecumenical recognition within communities, among churches, and in their common pastoral mission." - Fr. and Professor Radu Bordeianu, Duquesne University , and Orthodox theologian, Representative of the Greek Orthodox Metropolis of Pittsburgh, and Assistant Priest of Holy Trinity Greek Orthodox Church in Pittsburgh. "This book makes an important contribution to ecumenical ecclesiology." - Rev. Dr and Professor Sandra Beardsall, St Andrew's College , Canada and United Church of Canada Ordained Minister. "I find Dr. Lim's work a solid and necessary contribution to ecumenical work around the world." - Rev. Dr. and Professor Dominick D. Hanckle, Regent University , and priest of the Communion of Evangelical Episcopal Churches. "With penetrating analysis and creative suggestions, this monograph takes the talk about ecumenical recognition in a new level." - Professor Veli-Matti Kärkkäinen, University of Helsinki .